The Role of Social Capital in Business Survival: A Study on Angkringan Businesses in Ponorogo - Khusniati Rofiah; Ilma, Mughniatul (El-Barka, 2024)
In the beginning, the business needed only more financial capital. However, now, social capital is also vital in building a business. One business model that only requires a little financial capital but needs social capital is the angkringan business. Angkringan business in the Ir. H. Juanda Street area of Ponorogo is currently increasing. The survival of the angkringan business must be connected to the role of the Juanda Zone Perpek-5 Association, which houses the cooperative network between traders. This study aims to reveal how the form of social capital is used and the implications of social capital on the survival of angering businesses. This research is qualitative, with the type of field study research that uses a phenomenological approach and an interdisciplinary approach that utilises economics and social sciences. The results showed five forms of social capital employed in the angkringan business: networking, reciprocity, trust, norms and values, and proactive action. Second, using these forms of social capital has significant implications for the survival of the angkringan business, including capital, human resources, production, and marketing. At the same time, three kinds of strategies are used: active, passive, and network. Of the three methods, the network strategy is the primary strategy that will determine the survival of the angkringan business.